Corações partidos no porto de Gênova - Gambini, Roberto (Estudos Avançados, 2006)
THIS ESSAY searches for lost feellings: beginning with an historical presentation of recently unified Italy, under the threatening specter of joblessness - and the corresponding situation of post-slavery Brazil, in need of manpower, the focus of this paper is to capture the immigrants's soul, observing the dramatic situation of their transmigrations. Acknowledging the importance of music to constellate and express collective feelings, the author interprets some pieces of Verdis operas, alongside with, on a subjective level, family postcards exchanged between members of broken families, focusing on affective conflicts that eventually contributed to the making of the great Brazilian animic amalgam.